Rumen metabolism and digestibility in dairy cows offered diets with forest by-products - Irfan, Muhammad (2022)
Swedish dairy industry faced a cris i s of feed shortage in summer of 2018, followed by a dry autumn. The forage shortage was severe in some regions. During that period Swedish g overnment intervened by introducing a 1.2 billion SEK package to help farmers and since then research is being done to find alternative feed resources in case of climate change effects in the future. Sweden has a big matchstick industry that uses mainly aspen trees to produce matchsticks with the huge leftover a spen by products comprising of bark and wood. In this context , the present study has been conducted to determine the potential use of a spen tree by products as an alternative feed resource for lactating dairy cows. For this purpose, three lactating rum i n ally cannulated cows of s imilar age and days in milk were selected at L ö vsta R esearch S tation , Swedish U niversity of A griculture S ciences , Uppsala, Sweden. T he selected cows were used according to a Latin square design with three diets, and three periods of three weeks each, comprising two weeks for adaptation and the last week for sampling . All three diets contain ed 9.70 kg /day DM of concentrate , plus : 1) Control diet with approximately 12 kg DM /day g rass silage; 2) Wood diet with 6.7 kg DM /day grass silage and 4.1 kg DM /day ground aspen wood chips and 3) Bark diet with 6.7 kg DM /day grass silage and 4.6 kg DM /day ground aspen bark . During the sampling period (7 days) feed intake was calculated based on offered and refused feed quant it ies . Rumen evacuations , once per cow/treatment/period, were performed for the determination of the pools of dry matter, organic matter, and neutral detergent fiber . In addition, the ruminal liquid was sampled for pH. Fecal sample s w ere collected to determine the digestibility of feed by acid insoluble ash. Total dry matter intake was 21.86 kg/day for the control diet (p ≥ 0.08) as compared to wood and bark with 19.23 k g/day and 19.76 kg/day respectively. The crude protein intake was significant ly higher (p<0.02) for the control diet with 4.17 kg/day compared to 3.16 kg/day for the wood diet and 3.26 kg/day fo r the bark diet. Total NDF intake was not different (p ≥ 0.14) among treatments, with 9.42, 9.23 and 8.77 kg/day for control, wood, and bark diets, respectively . Dry matter digestibility did not diff p ≥0.31), being 67 % for the control diet and 65% for both wood and bark d iets . Milk yield was numerically higher (p ≥0.13) for the control diet 29.42 kg/day than for the wood diet ( 24.92 kg/day and bark diet ( 26.23 kg/day )). Rumen content kg on fresh weight FW) was similar for control and wood diets with 84.60 kg while it was numerically lower p ≥0.24) in the bark diet 77.80 kg The results for the ruminal content of DM and NDF tended to differ (p ≤ 0.10), wood being 0.10), wood being highehigherr, mean values 13.92 kg and 8.08 kg, , mean values 13.92 kg and 8.08 kg, than than bark 12.43 kg and 7.13 kg bark 12.43 kg and 7.13 kg andand to control to control dietdiet with mean 12.11 kg and 7.11 kg respectively.with mean 12.11 kg and 7.11 kg respectively. Results esults of the of the present present study suggeststudy suggest that thethat the use use of of aspen byaspen by--products products may represent anmay represent an alternativealternative source of source of roughageroughage at timeat timess of fodder shortage. It is highly recommendedof fodder shortage. It is highly recommended, however,, however, to to check the check the level of crude protein level of crude protein inin the dietthe dietss as itas it is is usually usually lowlow in in aspen byaspen by--products.products.